Annotated Checklist of Marine Amphipods (Crustacea: Amphipoda) of India - Thacker, Dimple; Patel, Krupal; Myers, Alan; Guerra-García, José M.; Zeidler, Wolfgang; Trivedi, Jigneshkumar (Zootaxa, 2023)
An annotated checklist of the marine amphipods recorded from Indian waters is compiled from the available peer-reviewed literature. A total of 266 species belonging to 133 genera and 56 families are listed. The maximum numbers of species were recorded from the South Indian Ecoregion (177 species, 98 genera, 47 families), followed by the Western India Ecoregion (101 species, 72 genera, 36 families), the Eastern Indian Ecoregion (99 species, 65 genera, 35 families), the Northern Bay of Bengal Ecoregion (92 species, 53 genera, 29 families), the Maldives Ecoregion (32 species, 24 genera, 16 families), and the Andaman and Nicobar Islands Ecoregion (31 species, 22 genera, 18 families). Notes on the questionable identifications and records of some amphipods are also provided.